Islamic Leadership dan Pelibatan Masyarakat Sebagai Faktor Terpenting Dalam Membangun Sistem Manajemen Mutu Masjid - Rahadi Mulyanto; Mohammad Izdiyan Muttaqin (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
Quality Management is a management system used to maintain the best service quality, and the outcome is customer satisfaction and loyalty. As one of the public service centers, Mosques are a time to focus on implementing quality management to improve the best service for their worshippers. In Islamic history, the Prophet SAW has applied the fundamental basis of quality management, especially during the establishment and operation of the Prophet's mosque in Medina: Islamic leadership and community involvement. These two factors are currently crucial in building a quality management system. This study aims to map mosques' business processes (activities) to create a quality management system. The research method uses qualitative research design with a phenomenological approach, followed by descriptive historical-comparative method analysis. The study found findings of mosque leadership models, community involvement models, and conclusions of congregational behavior, cultural behavior, social behavior, personal behavior, and psychological behavior. Then there were also findings of issues findings from internal and external problems around the mosque, and the final part was the finding of expectations from mosque worshippers and how the mosque prepared a strategic strategy to respond to the expectations of the congregation; furthermore, the critical point of the results of this study was found a business map model of mosque processes (activities) which became the essential element to build a mosque quality management system.Keywords – Community Involvement, Context Organization and Business Process, Islamic Leadership, Quality Management.